THE IMPACT TEACHER PROFESSIONAL DEVELOPMENT PROGRAM IN INDONESIA ON SCIENCE TEACHERS’ KNOWLEDGE AND PRACTICE: A REVIEW AND CRITIQUE - Kasi, Yohanes Freadyanus; Samsudin, Achmad; Widodo, Ari; Riandi, Riandi; Nurtanto, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this article is to provide a review of empirical studies investigating the impact of teacher professional development (TPD) program in Indonesia on science teachers’ knowledge and practices. Across 11 articles that satisfied the definition we embraced, most were devoted to the improve the content knowledge (CoK/CK), general pedagogical knowledge (GPK), pedagogical content knowledge (PCK), and science teaching practices. Although a small number of studies have an implicit focus on variable affective, we set out to examine the studies in science education. Analysis of the related studies resulted in the following the TPD program in Indonesia can help teachers improving their CoK/CK, GPK, PCK, and may facilitate the change in teacher practices, science teachers’ activities focusing on student learning in TPD program are more likely to change their practice. However, based on the analysis the TPD program in Indonesia still lacks using a partnership approach, technology, and ethnoscience. The recommendation for further research is still needed to more fully justify the expansion of the TPD program in Indonesia for science teachers using a partnership approach, technology, and ethnoscience to increase knowledge of the TPD program and their role to improve science teaching and learning in class.